A taxonomic revision of Chinese Cleopomiarus Pierce (Coleoptera: Curculionidae) with description of two new species - Jiang, Chunyan; Caldara, Roberto; Zhang, Runzhi (Zootaxa, 2018)
The Chinese species of Cleopomiarus Pierce, 1919 (Curculionidae, Curculioninae, Mecinini) are revised. Six taxa are reported: two already know from China (C. distinctus (Boheman, 1845), C. vestitus (Roelofs, 1875)), two cited for the first time from this country (C. flavoscutellatus (Morimoto, 1959), C. graminis (Gyllenhal, 1813)), and two new to science (C. danfengensis Jiang & Caldara n. sp., C. nuerhachii Jiang & Caldara n. sp.). The following new synonymy is proposed: C. distinctus (Boheman, 1845) = Miarus longirostris mandschuricus Voss, 1952 n. syn. Diagnosis, description or redescription, comparative notes and distribution are reported for each species. Dorsal and lateral habitus, as well as details of rostra and genitalia are illustrated. Finally, a key to the species is provided. Type specimens are deposited in the National Zoological Museum of China in the Institute of Zoology, Chinese Academy of Sciences in Beijing, China.